Nontypeable Haemophilus influenzae exploits the interaction between protein-E and vitronectin for the adherence and invasion to bronchial epithelial cells. Issue 1 (December 2015) - Ikeda, Masaki; Enomoto, Noriyuki; Hashimoto, Dai; Fujisawa, Tomoyuki; Inui, Naoki; Nakamura, Yutaro; Suda, Takafumi; Nagata, Toshi
Abstract Background NontypeableHaemophilus influenzae (NTHi) is one of the most common Gram-negative pathogens in otitis media and exacerbation of chronic obstructive pulmonary disease. NTHi has been reported to invade bronchial epithelial cells. This penetration enables NTHi to evade the host immune system and antibiotics, and it seems to be related to the intractable features of these diseases. However, the precise mechanism of the invasion has been unknown. We hypothesized that protein-E, an outer membrane protein of NTHi, plays a role in this penetration into bronchial epithelial cells. Results We utilized two NTHi strains. NTHi efficiently attached to plate-bound vitronectin (254–309 / field at 1, 000× magnification) and this attachment was blocked by pretreatment with protein-E peptide (PE84–108 ). The blockade of adhesion was dependent on the concentration of PE84–108 . NTHi strains invaded bronchial epithelial cells and the intracellular bacteria were localized in early endosomes. Furthermore, intracellular invasion of NTHi was also blocked by PE84–108, but not by Arg-Gly-Asp (RGD) peptide. Pretreatment with PE84–108 significantly prevented cells from being invaded by both NTHi strains, which was confirmed by fluorescent microscope observation. In addition, pretreatment with PE84–108 significantly reduced percentages of CFU after gentamicin treatment of cells per input CFU. Conclusions These results suggest that NTHi does not directly bind to the cell surface, but binds to host vitronectin that is bound to the cell surface, via bacterial protein-E. Bacterial protein-E and host vitronectin play a role in the attachment to bronchial epithelial cells and is also involved in the subsequent intracellular invasion of NTHi. A novel vaccine or treatment strategy targeting the protein-E-vitronectin axis may prevent respiratory intracellular infection of NTHi and may lead to better clinical outcomes.